2005
DOI: 10.1007/bf02835784
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study on the treatment of chronic pelvic inflammation of Qi-stagnation with blood stasis syndrome by Penyanqing Capsule

Abstract: PYQC has good therapeutic effect in treating chronic pelvic inflammation of Qi-stagnation with blood stasis syndrome, and showed definite effect on chlamydia and mycoplasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As a branch of TCM, TCM gynecology and TCM gynecological nursing has developed precociously according to the record in The Yellow Emperor of Classics of Inner Medicine. Nowadays gynecology and gynecological nursing in TCM are still beneficial to woman [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…As a branch of TCM, TCM gynecology and TCM gynecological nursing has developed precociously according to the record in The Yellow Emperor of Classics of Inner Medicine. Nowadays gynecology and gynecological nursing in TCM are still beneficial to woman [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…① Cured: after drug intervention, various clinical symptoms disappeared, such as pelvic masses, tender nodules and other local signs basically disappeared. The percentage of efficacy (N) is greater than or equal to 95% [9].…”
Section: Information and Methodsmentioning
confidence: 99%
“…[7] Research on BSS has improved since 1989, with the establishment of the standard diagnosis criteria for BSS. It is reported that BSS is correlated to several pathogeneses including abnormal coagulation function, [8] inflammation, [9] and accelerated red blood cell senescence. [10] Studies that focus on the treatment of BSS are also increasing.…”
Section: Introductionmentioning
confidence: 99%